USE OF PREDICTORS TO CHOOSE TREATMENT POLICY FOR THYROID CANCER - V. Zh. Brzhezovsky,; M. V. Lomaya; T. A. Aketova (Опухоли головы и шеи)
The paper analyzes the results of treatment in patients with papillary thyroid cancer, by applying a great deal of clinical material. Different prognostic factors have been studied for their influence on the survival of the patients after surgical treatment. The most optimal treatment policy is proposed to be defined for patients with this form of cancer on the basis of the association between the above factors.